Combining ability and heterobeltiosis for yield and yield contributing traits in high quality oil Indian mustard (Brassica juncea) genotypes - SINGH, NAVEEN; YADAVA, D K; VASUDEV, SUJATA; SINGH, RAJENDRA; GIRI, S C; DASS, B; BARUN, SIDDHARTHA; PRABHU, K V (The Indian Journal of Agricultural Sciences, 2015)
Heterosis and combining ability estimates were worked out using Line × Tester analysis of 72 hybrids developed by crossing 12 lines with 6 testers including four double zero, ten single zero and four conventional Indian mustard [Brassica juncea (L.) Czern. & Coss.] genotypes. Analysis of variance revealed sufficient differences among parents, hybrids and parent vs. hybrids for most of the traits studied. Both additive and non additive type of gene effects for seed yield and yield related traits were observed. Estimates of GCA effects indicated that Pusa Mustard 22, Pusa Mustard 29, Pusa Agrani, EC 597318 and Pusa Karishma were good general combiners. One hybrid low in erucic acid and glucosinolates content (PDZ 3 × EC 597318), six low in erucic acid content (Pusa Mustard 22 × Pusa Karishma, Pusa Mustard 24 × Pusa Karishma, EC 597325 × Pusa Karishma, TERI M 21 × EC 597318, ELM 132 × EC 597318, Pusa Mustard 29 × Pusa Mustard 21) and six conventional hybrids (EC 597325 × Pusa Agrani, RH(00)7003 × Varuna, ALM 936A × Varuna, Pusa Musatrd 29 × Pusa Agrani, Pusa Tarak × Pusa Mustard 21 and PDZ 3 × Varuna) had significantly high sca effects, >15% heterobeltiosis and high per se performance for seed yield/plant. These high quality oil genotypes involved in developing heterotic hybrids, in this study, shall be converted to cytoplasmic male sterile and/or restorer lines. Identified high yielding cross combinations can further be exploited for improving the yield and quality of Indian mustard.